Thermal comfort in the modern movement - consequences of constructive definition on the summer behaviour of a housing building in Porto, Portugal - Silva, I. (2021)
The knowledge of the properties of construction materials, as well as the way they are organized in the construction systems, namely those of the facades, are essential to understand the functional performance of buildings, namely their thermal comfort. This article presents a research oriented towards the constructive characterization of the facades of a multifamily building and the consequences for its thermal comfort in summer. The building here analysed is Edifício Lino, built between 1951 and 1954 in Porto, designed by the architects Arménio Losa and Cassiano Barbosa, prominent figures in the architecture of the modern movement in Portugal. The importance of studying buildings at this time is related to the need to define strategies for use, maintenance and possible intervention in the existing heritage in order to respond to the contemporary expectations of habitability of these works of the Modern Movement, often forgotten due to the temporal proximity. From the study carried out, it can be concluded that thermal comfort emerges as a central concern of the reference architects of this time, who considered this issue an inexorable architectural quality.